Laser-plasma coupling in the shock-ignition intensity regime - Antonelli, L; Batani, D; Patria, A; Ciricosta, O; Cecchetti, C; Koester, P; Labate, L; Giulietti, A; Gizzi, L; Moretti, A; Richetta, M; Giuffrida, L; et al. (2011)
A novel approach to ICF called shock ignition, that relies on delivery of a very strong shock created by a laser pulse at intensities around 10 16 W cm-2, is investigated. In this context, an experiment using two beams from the Prague Asterix Laser System with time duration of 300 ps was performed at the PALS laboratory. The first beam at low intensity was used to create extended preformed plasma, and the second one to create a strong shock. Several diagnostics were used to characterize the preformed plasma and the interaction of the main pulse with the target. © 2011 Institute of Thermomechanics AS CR, v.v.i.